Rational design of functionalized polyacrylate-based high internal phase emulsion materials for analytical and biomedical uses. Issue 48 (23rd November 2016) - Brusotti, Gloria; Calleri, Enrica; Milanese, Chiara; Catenacci, Laura; Marrubini, Giorgio; Sorrenti, Milena; Girella, Alessandro; Massolini, Gabriella; Tripodo, Giuseppe
Abstract : Functional polyacrylate-based materials rationally designed by high internal phase emulsion (polyHIPE) are reported. Abstract : This paper deals with the preparation of new poly(High Internal Phase Emulsion) [polyHIPE] materials, templated by varying different preparation parameters. The obtained systems are based on acrylic monomers, polymerized by free radical polymerization initiated by potassium persulfate and the redox initiator N, N, N ′, N ′-tetramethylethylenediamine (TEMED) to gain a crosslinked system at room temperature. To get a functional material, glycidyl methacrylate (GMA) has been introduced in the polymeric structure. The HIPE system was effectively stabilized by a co-polymer surfactant, while a polysorbate surfactant did not stabilize the emulsion. Water as the internal phase with its content ranging from 80 to 90% was explored. A deep characterization of the materials, including SEM, DSC, TGA, BET, swelling and weight loss was carried out. The developed systems are promising and can find successful applications for analytical and biomedical purposes.